O público e o privado no ensino superior brasileiro: do regime militar (1964 1984) ao Governo FHC (1995 2002) - Peres, Claudio Afonso (2009)
This study addresses the relationship between the public and the private in the context of the reforms implemented in the Brazilian higher education from the second half of the 20th century on, which resulted in the expansion of the private education sector, mainly during the Brazilian Military Regime (1964-1984) and the Fernando Henrique Cardoso administration (1995-2002). The study aims at examining the historical role of the Brazilian State in funding and maintaining the higher education, considering the political and economic context in both moments, as well as the relationship between State and society (bourgeoisie and working class) and the market. This understanding is achieved by the analysis of the reforms, legislation, works of classic and contemporary authors, official documents, in addition to the analysis of the correlation of forces established in each moment. The study also seeks to interpret the foreign influence that can be identified in the performance of the international organizations related to the issue of funding and to the guidelines for the educational policies in the context of higher education. It is considered a major problem for the Brazilian working class the fact that the percentage of private institutions of higher education has reached the rate of 89% in 2006. In fact, at the end of the Military Regime, in 1985, this rate had already reached 73%. The dissertation is organized in three chapters: the first one is dedicated to some theoretical concepts, the historical context and the laws that reform the State and the higher education and that demonstrate the private nature of education; in the second chapter, relevant topics (politics, economy, social movements and the foreign influence) are discussed and related to education; and, finally, the third chapter addresses the public and the private in the higher education and the relations with the market as a consequence of the historical and theoretical aspects previously analyzed, and considerations are also made on the civil-military nature of the Regime and the transition period between the Military Regime and the Fernando Henrique Cardoso administration. The text is presented in a sequence that enables the resource to topics previously addressed, since along the study several concepts that complete the information and improve the understanding of the object are recovered. The arguments presented in this study consist of theses and antitheses, which form summaries that can be related to future events, but that are still linked to the past. Thus, in addition to analyzing and comparing two different historical periods, which present contrasts and elements of continuity, the study seeks to maintain the view of the totality, considering the endogenous and exogenous factors that influenced the privatization process of Brazilian higher education.